The Effect Of Liquidity And Solvency On Profitability In Pt. Kalbe Farma Tbk - Della Maretha; Vivin Tri Astuti; Khusnik Hudzafidah; Joni Hendra; Dede Hertina (Jurnal Info Sains : Informatika dan Sains, 2023)
The research objective was to determine the effect of liquidity and solvency on profitability at PT. Kalbe Pharmacy. The data used in this study is secondary data, namely time sequence data or time series data using the documentation method, namely collecting data from previous records. Data analysis used in this research is quantitative analysis and the analysis technique used is multiple regression analysis technique. The variables used in this study are liquidity (CR) and solvency (DER) as independent variables and profitability (GPM) as the dependent variable. Based on the results of the analysis of liquidity (CR) and solvency (DER) have a significant influence on the profitability (GPM) of PT Kalbe Pharma Tbk.